Gender equality through women's empowerment strategies and approaches - International Conference on Gender Equality Through Women's Empowerment: Strategies and Approaches Lucknow, India) (1997; Singh, Surendra 1943 Dec. 5.; Srivastava, S. P. 1940-. (Lucknow Bharat Book Centre, 2001)
Contributed articles presented at the International Conference on Gender Equality Through Women's Empowerment: Strategies and Approaches on March 7-9, 1997, Lucknow, India with special focus on Indian situations.
Keywords: Women in development -- India -- Congresses; Women -- Social conditions -- India -- Congresses; Women -- Economic conditions -- India -- Congresses